IbM of Small Medium Enterprise of Coconut Milk and Liquid Smoke from Coconut Shells - Yusraini, Era; Halimatuddahliana; Gea, Saharman (Journal of Saintech Transfer, 2018)
Community service activities funded by BPPTN 2017 has been implemented with one of the partners, who was a small entrepreneur of coconut milk and liquid smoke from coconut shells, held from August to November 2017. Partnership of community service was Mr. Budi Darmanto, who has has his business for 9 years in Medan. The problems facing by the partner were: marketing of the coconut milk was still through the agent, resulting in the low selling price because the cost must be cut off for agent commission. In addition, liquid smoke product from coconut shells still contained impurity (Tar), classified as grade 3, causing the demand and its selling price became low. Solutions to the problems were 1) opening or enlarging the new commercial market for coconut milk, by assisting them in the handling of halal permits to the MUI of North Sumatra Province and made marketing advertisements through the website; 2) Providing a grant of liquid smoke distillation apparatus, making standard operational procedures (SOPs) to reduce impurities as well as increasing the grade of liquid smoke, to increase the selling price, and also analyzing the quality of distillated liquid smoke. The opening of commercial market of coconut milk and increasing grade of liquid smoke is expected to increase the partner’s income and expand his own business.